Basic flows of generalized second grade fluids based on a Sisko model - Walicka, Anna (Zielona Góra: Uniwersytet Zielonogórski)
The present investigation is concerned with basic flows of generalized second grade fluids based on a Sisko fluid. After formulation of the general equations of motion three simple flows of viscoplastic fluids of a Sisko type or fluids similar to them are considered. These flows are: Poiseuille flow in a plane channel, Poiseuille flow in a circular pipe and rotating Couette flow between two coaxial cylinders. After presentation the Sisko model one was presented some models of fluids similar to this model. Next it was given the solutions of equations of motion for three flows mentioned above.
Keywords: Sisko fluids; similar fluids; simple flows